Food Law and Regulation for Non-Lawyers A US Perspective - Sanchez, Marc C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
Designed and modeled after a six-week introductory food law course taught at Northeastern University, Food Law and Regulation for Non-Lawyers offers a succinct overview of key topics and core concepts for food scientists, quality managers, and others who need to understand the regulation of food in the U.S. This second edition includes critical updates on the Food Safety Modernization Act-- the first change to the food safety laws in over 70 years. The seven foundational rules, finalized in 2015, are discussed in detail. The new edition also includes other regulatory updates such as the new Nutrition Fact Panel, changes to the definition of fiber, and the FDA's attempt to regulate the widely used "healthy" claim. These timely updates, along with the core concepts of the first edition, make the volume an essential and practical tool for regulatory professionals.
1. Introduction to Statutory Framework and Case Law -- 2. Federal Inspection and Enforcement -- 3. Adulteration -- 4. Misbranding -- 5. Food Safety Modernization Act 6. Regulation of Dietary Supplements and Other Specialized Categories -- 7. Food Additives -- 8. Private Actions and Personal Liability.
Keywords: Public law .; Food science; Public health; Environmental law, International; Public Law; Food Science; Public Health; International Environmental Law